STRUCTURAL FEATURES OF FOREIGN ECONOMIC RELATIONS OF THE REPUBLIC OF ARMENIA (Proceedings of the YSU C: Geological and Geographical Sciences, 2014)
The article examines the structural features of foreign economic relations of the Republic of Armenia, an attempt is made to identify their possible areas of development, causes of export reduction and import increasing in major commodity groups, are characterized and makes proposals to improve transport links with other countries of the region.
Keywords: import substitution; geo-economics; globalization; foreign trade; domestic production; competitiveness